2019
DOI: 10.2520/myco.69-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aflatoxin production by protein tyrosine phosphatase inhibitors, blasticidin A and dephostatin

Abstract: Blasticidin A, a Streptomyces metabolite, inhibits aflatoxin production in aflatoxigenic fungi. The mode of action of blasticidin A in the inhibition of aflatoxin production was investigated. Blasticidin A inhibited human PTP1B (a protein tyrosine phosphatase) with the IC 50 value of 27 µM, but not human PP1A (a protein serine/threonine phosphatase). Dephostatin, a known protein tyrosine phosphatase inhibitor, inhibited aflatoxin production without affecting fungal growth. Blasticidin A delayed expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, the majority of studies in this area are focused on biodegradation aspects, whereas the search for potential efficient inhibitors of mycotoxin production among natural compounds of plant or microbial origin seems to be underestimated. To date, the number of such studies is relatively low, and these are mainly focused on the AFB1 biosynthesis inhibitors (see, for example, [ 40 , 41 ]). Moreover, some compounds reported to suppress mycotoxin biosynthesis also possess antifungal activity; thus, it often remains unclear if they reduce mycotoxin content via suppression of its biosynthesis, or simply by reducing the mycelial biomass producing them.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of studies in this area are focused on biodegradation aspects, whereas the search for potential efficient inhibitors of mycotoxin production among natural compounds of plant or microbial origin seems to be underestimated. To date, the number of such studies is relatively low, and these are mainly focused on the AFB1 biosynthesis inhibitors (see, for example, [ 40 , 41 ]). Moreover, some compounds reported to suppress mycotoxin biosynthesis also possess antifungal activity; thus, it often remains unclear if they reduce mycotoxin content via suppression of its biosynthesis, or simply by reducing the mycelial biomass producing them.…”
Section: Discussionmentioning
confidence: 99%
“… Yan et al (2004) showed that Achromobacter xylosoxidans secreted cyclic dipeptide cyclo(L-leucyl-L-prolyl) along with cyclo(D-leucyl-D-prolyl) and cyclo(L-prolyl-Lvalyl) inhibited the aflatoxin production from Aspergillus parasiticus . Inoguchi et al (2019) reported that both blasticidin A inhibited the aflatoxin biosynthesis which acts as protein tyrosine phosphatase inhibitors which in turn can perform as potential aflatoxin production inhibitors.…”
Section: Amino Acid-based Inhibitionsmentioning
confidence: 99%
“…This indicated that the antimicrobial activity of BcA was related to its protein synthesis inhibitory activity. In subsequent research, the inhibitory activity of BcA against a protein serine/threonine phosphatase was found 8) . The relationship between the phosphatase and protein synthesis is now in progress.…”
Section: Aflatoxin Production Inhibitors (Fig 2) 1) Blasticidin Amentioning
confidence: 99%